(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
Application of dyes is prevalent in industries involved in textile and food manufacturing. Effluent discharge from these industries to neighbouring water bodies cause significant health concerns due to dye toxicity. To date, only very few bacteria are isolated with the ability to completely assimilate dyes. The main objective of this study is to isolate bacteria(s) with the ability to utilise reactive red dye 120. Local strains were isolated from contaminated sites in Northern Malaysia. Based on 16S rDNA gene sequence analysis, the best strain was identified as Pseudomonas sp. strain DRY011. Optimum RR120 decolourisation was observed at 200 ppm with 71.07% removal rate within 5 days and able to tolerate up to 500 ppm. The effect of heavy metals (silver, arsenic, cadmium, chromium, copper, mercury, lead and zinc) were investigated. Mercury, 1 ppm had the highest inhibition effect, followed by zinc and silver, with decolourisation of 12 % and 14.3 % respectively. Chromium had the least effect with 55.6% decolourisation and bacterial growth of 11.5 CFU/mL. The rest of the heavy metal had the least effect on the decolourisation rate. As a conclusion, the finding of microbial degrader able to utilise dye will become crucial bioremediation key in controlling the level of dye wastes in water bodies.